A new species and new record of Bulbophyllum (Orchidaceae) from Vietnam - Pham, Phuoc Dien; Averyanov, Leonid V.; Dang, van Son; Nguyen, Dinh Hiep; Maisak, Tatiana; Truong, Quang Tam; Dang, Minh Quan; Truong, Ba Vuong (Phytotaxa, 2021)
The new species, Bulbophyllum manhdatii (B. sect. Brachyantha) discovered in Da Lat Plateau, Lam Dong Province (southern Vietnam) is described here. This new species is close to B. pumilio but clearly differs in densely crowded pseudobulbs and their shape, shorter inflorescence, lateral sepals forming a narrow acute tube slightly flattened at the base, lip without median keel, and longer stelidia. In addition, a new national record, B. seidenfadenii, from the same section is also reported from the first time from North Vietnam.